Anti-neuroinflammatory effects of Cleistocalyx nervosum var. paniala berry-seed extract in BV-2 microglial cells via inhibition of MAPKs/NF-κB signaling pathway. Issue 11 (November 2022) - Janpaijit, Sakawrat; Lertpatipanpong, Pattawika; Sillapachaiyaporn, Chanin; Baek, Seung Joon; Charoenkiatkul, Somsri; Tencomnao, Tewin; Sukprasansap, Monruedee
Abstract: Neuroinflammation is an essential contributor to multiple neurodegenerative disorders. Cleistocalyx nervosum var. paniala, an edible berry, has been reported to exhibit a neuroprotective effect. However, only limited research is available on this fruit seed, which is classified as agricultural food waste. We therefore focused on the anti-neuroinflammatory effects and mechanisms of C. nervosum var. paniala seed extract (CNSE) on lipopolysaccharide (LPS)-induced inflammatory response in BV-2 mouse microglial cells. HPLC analysis showed that CNSE consists of resveratrol (RESV). For cell-based studies, BV-2 cells were pre-treated with CNSE or RESV, followed by LPS. We found that CNSE and RESV inhibited LPS-induced inflammation in a dose-dependent manner. CNSE and RESV inhibited gene expression and activity of iNOS, leading to a decrease in nitric oxide production. Both CNSE and RESV suppressed the gene expression and the activities of TNF-α, IL-1β, and IL-6. Our results revealed that LPS stimulated the protein levels of MAPKs (JNK, ERK1/2, and p38), while pretreatment of cells with CNSE or RESV attenuated these proteins expressions. CNSE also suppressed NF-κB activation. These results suggest that CNSE and RESV can inhibit LPS-induced inflammatory response through MAPKs/NF-κB pathways in BV-2 cells. Taken together, CNSE have potential as a functional anti-neuroinflammatory agent. Abstract : Lipopolysaccharide; MAPKs; Microglial cells; Neuroinflammation; NF-κB.